HUBUNGAN KOMPETENSI PEDAGOGIK GURU DAN PEMBELAJARAN INOVATIF DENGAN MOTIVASI BERPRESTASI SISWA KELAS V - Diana Afifa; Asrin; Muhammad Sobri (Renjana Pendidikan Dasar, 2023)
The lesson plan and implementation of the lesson made by the class V teacher only used one learning strategy during one semester's learning and also used assignment, observation, question and answer, discussion and lecture methods. Learning must be innovative in order to create fun learning and increase student achievement motivation. The aims of this study were 1) to determine the relationship between teacher pedagogic competence and student learning motivation, 2) to determine the relationship between innovative learning and student achievement motivation, 3) to determine pedagogical competence and innovative learning and student achievement motivation. The method used is multiple correlation analysis method. The location of the research was at SDN Gugus IX Praya Central Lombok in the even semester. The results of this study are that there is a positive and significant relationship between teacher pedagogical competence and innovative learning with the achievement motivation of fifth grade students of Public Elementary Schools Group IX Praya. Suggestions for school principals and teachers are to continue to improve teacher competence through training, as well as for other researchers to review similar research related to student achievement motivation.